2015
DOI: 10.3390/molecules20059242
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic Acid Phenethyl Ester and Ethanol Extract of Propolis Induce the Complementary Cytotoxic Effect on Triple-Negative Breast Cancer Cell Lines

Abstract: Chemotherapy of breast cancer could be improved by bioactive natural substances, which may potentially sensitize the carcinoma cells' susceptibility to drugs. Numerous phytochemicals, including propolis, have been reported to interfere with the viability of carcinoma cells. We evaluated the in vitro cytotoxic activity of ethanol extract of propolis (EEP) and its derivative caffeic acid phenethyl ester (CAPE) towards two triple-negative breast cancer (TNBC) cell lines, MDA-MB-231 and Hs578T, by implementation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 56 publications
2
42
0
1
Order By: Relevance
“…Several researches have shown the anticarcinogenic and proapoptotic effects of CAPE, but little is known regarding Caf effects. CAPE and Caf are different molecules with different physical, chemical and functional properties.…”
Section: Discussionmentioning
confidence: 99%
“…Several researches have shown the anticarcinogenic and proapoptotic effects of CAPE, but little is known regarding Caf effects. CAPE and Caf are different molecules with different physical, chemical and functional properties.…”
Section: Discussionmentioning
confidence: 99%
“…Today, the positive contribution of propolis to health, which are via its antimicrobial, anti-inflammatory, regenerative, immunomodulatory, antioxidant and antimutagenic effects have been proven by scientific studies (1)(2)(3)(4)6). One of the most important biological attributes of propolis has been pointed out by various studies to be the anticarcinogenic effects (5,7,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, although it was not investigated in this study, a derivate of caffeic acid, CAPE is considered a major pharmaceutical component of propolis (49) and evaluated more extensively in the literature. CAPE was reported to inhibit the growth of the BCCLs, MDA-MB-231 (28,29), Hs578T (28), MCF-7 (29), and SK-BR-3 (29) in a dosedependent and exposure time-dependent manner (28). It was also reported that CAPE reduces expression of growth and transcription factors, including NF-κB (50) and induces cell cycle arrest and apoptosis (51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the mechanism of action of a novel bisnaphthalimidopropyl derivative, BNIPDaCHM, was investigated in one of the most commonly studied poly(ADP-ribose) polymerase inhibitors [32], and also, propolis and its derivative caffeic acid phenethyl ester [33], to name a few.…”
Section: Discussionmentioning
confidence: 99%